In Vitro Corrosion and Tribocorrosion Performance of Biocompatible Carbide Coatings - Pana I. Iulian; Vladesku A. Alina; Constantin L. R. Lidia; Sandu I. G. Ioan; Dinu M. Mihaela; Cotrut C. M. Cosmin (2020, 2020)
Title screen